Positive systems : theory and applications (POSTA 2016) Rome, Italy, September 14-16, 2016 - Cacace, Filippo; Farina, Lorenzo, 1963-; Setola, Roberto; Germani, Alfredo (Springer, 2017)
This book presents high-quality original contributions on positive systems, including topics such as: monotone dynamical systems in mathematical biology and game theory; mathematical developments for networked systems in biology, chemistry and the social sciences; linear and nonlinear positive operators; dynamical analysis, observation and control of positive distributed parameter systems; stochastic realization theory; biological systems with positive variables and positive controls; iterated function systems; nonnegative dynamic processes; and dimensioning problems for collaborative systems. The book comprises a selection of the best papers presented at the POSTA 2016, the 5th International Symposium on Positive Systems, which was held in Rome, Italy, in September 2016. This conference series represents a targeted response to the growing need for research that reports on and critically discusses a wide range of topics concerning the theory and applications of positive systems.
Keywords: Positive systems -- Congresses.; Non-negative matrices -- Congresses.; Mathematical models -- Congresses.; elektronické knihy; electronic books